2005
DOI: 10.1110/ps.051604805
|View full text |Cite
|
Sign up to set email alerts
|

Structure of MurF from Streptococcus pneumoniae co‐crystallized with a small molecule inhibitor exhibits interdomain closure

Abstract: In a broad genomics analysis to find novel protein targets for antibiotic discovery, MurF was identified as an essential gene product for Streptococcus pneumonia that catalyzes a critical reaction in the biosynthesis of the peptidoglycan in the formation of the cell wall. Lacking close relatives in mammalian biology, MurF presents attractive characteristics as a potential drug target. Initial screening of the Abbott small-molecule compound collection identified several compounds for further validation as pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 25 publications
1
63
0
Order By: Relevance
“…Furthermore, the open and closed X-ray structures of free and complexed MurD [11e13] and MurF [14,15] show that the Cterminal domain undergoes substantial conformational changes upon substrate or inhibitor binding [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the open and closed X-ray structures of free and complexed MurD [11e13] and MurF [14,15] show that the Cterminal domain undergoes substantial conformational changes upon substrate or inhibitor binding [16].…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structures of MurF from E. coli (30) and S. pneumoniae (14) indicate that these are monomeric enzymes with multiple domains; it is possible that some of the binding compounds alter domain interactions, stabilizing the protein without inhibiting the enzyme. Since the ThermoFluor assay identified compounds that produced an increase in MurF T m , presumably by binding to and stabilizing the protein, it is unlikely that the compounds that inhibited MurF activity act by causing protein denaturation, since denaturation should decrease the MurF melting temperature.…”
Section: Discussionmentioning
confidence: 99%
“…These include a nonhydrolyzable ATP analog (1) and phosphinate transition state analogs (16). Gu et al have reported on a series of sulfonamides (11), and Longenecker et al have cocrystallized an inhibitor with Streptococcus pneumoniae MurF (14). In addition, we have reported on a series of thiazolylaminopyrimidines that inhibit Escherichia coli MurF (2).…”
mentioning
confidence: 99%
“…Eleven unique compounds were identified by this method as potential inhibitors. Fortunately, MurF was very amenable to NMR techniques, providing readily interpretable 1 H/ 13 C-HSQC spectra [34]. Thus, solution-phase NMR was used to triage the list of AS/MS hits and corroborated the binding of two (Fig.…”
Section: Triage Of Initial Leadsmentioning
confidence: 99%